Comparative analysis of Respiratory Syncytial Virus frequency rates and viral load in different patient cohorts in a University Hospital in São Paulo, Brazil, over an eight-year period (2005–2013) - Luciano Kleber de Souza Luna; Jessica Santiago Cruz; Tânia do Socorro Souza Chaves; Nancy Bellei (Brazilian Journal of Infectious Diseases, 2023)
Respiratory Syncytial Virus (RSV) poses a global health concern, particularly affecting young children, the elderly, and immunosuppressed individuals. RSV viral load is essential for understanding transmission, disease severity, prevention, and treatment. This retrospective study aimed to analyze the frequency rates and viral loads of RSV infections in different patient cohorts and age groups over an eight-year period in a university hospital in São Paulo, Brazil. This study analyzed 1380 Immunocompetent (IC) and Immunosuppressed (IS) patients with acute respiratory tract infections. IC included patients with chronic Heart Disease (HD), Primary Care service recipients (PC), and a subgroup suspected of having Severe Acute Respiratory Syndrome caused by Influenza A (H1N1)pdm09 virus (SARS H1N1). IS comprised transplant patients and those with HIV infection. Respiratory samples were collected between February 2005 and October 2013, with RSV detection and viral load quantification (Log10 copies of RNA/mL) using RT-qPCR. Overall RSV infection rate was 17.3 %, with higher rates in children (23.9 %) than in adults (12.9 %), particularly in children under two years of age (28.2 %). Children in the SARS H1N1 and PC subgroups had higher infection rates (16.4 % and 34.9 %, respectively), with the highest rate in PC children aged 1 to < 2 years (45.45 %). Adults with HD had a significantly higher frequency rate (27.83 %) than those in the SARS H1N1 (2.65 %) and IS (15.16 %) subgroups and higher hospitalization rate among adults under 65 years. RSV viral load ranged from 2.43 to 10.15 Log10 RNA copies/mL (mean ± SD 5.82 ± 2.19), with hospitalized patients exhibiting significantly higher viral loads (7.34 ± 1.9) than outpatients (4.38 ± 1.89). Elderly bone marrow transplant patients also had significantly higher viral loads (7.57 ± 2.41) than younger adults (5.12 ± 1.87). This study provides insights into the RSV infection patterns in different patient cohorts in Brazil. Further investigations are needed to understand susceptibility and risk factors associated with RSV infection. In conclusion, high RSV viral load among hospitalized patients could serve as a surrogate marker of disease severity. Additionally, patients with chronic heart disease deserve greater attention regarding complications associated with RSV infection.